2020
DOI: 10.7759/cureus.10738
|View full text |Cite
|
Sign up to set email alerts
|

Immature Teratoma of the Palm: A Rare Site of Presentation

Abstract: Extragonadal teratomas in adults are an extremely rare entity. Teratomas may be mature or immature and are characterized by their midline presentation. We are presenting here a case report of immature teratoma of the palm in a 35-year-old female. The patient developed a recurrent swelling of the palm from which a wedge biopsy was taken and sent for histopathological examination. A diagnosis of “immature teratoma, grade 2” was made, whose margins were compromised. Later on ultrasonography (USG) abdomen and pelv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Coli et al 7 described an immature teratoma arising from the left posteroinferior thigh of an 86-year-old lady in the absence of clinical and radiological evidence of ovarian or any other tumor which was also managed by upfront surgical resection. Another case of immature teratoma in the palm similar to ours was described by Rajpoot et al, 8 where a diagnostic biopsy was done which revealed characteristic histopathological features and the patient was referred elsewhere with no follow-up details available. All reported presentations were in extremity with or without regional nodal involvement without the presence of an evident disease in the gonads.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Coli et al 7 described an immature teratoma arising from the left posteroinferior thigh of an 86-year-old lady in the absence of clinical and radiological evidence of ovarian or any other tumor which was also managed by upfront surgical resection. Another case of immature teratoma in the palm similar to ours was described by Rajpoot et al, 8 where a diagnostic biopsy was done which revealed characteristic histopathological features and the patient was referred elsewhere with no follow-up details available. All reported presentations were in extremity with or without regional nodal involvement without the presence of an evident disease in the gonads.…”
Section: Discussionsupporting
confidence: 70%
“…Only seven cases have been reported in literature so far (►Table 1). [2][3][4][5][6][7][8] Few reported sites of extremity GCT are arm, 5 thigh, 6,7 humerus, 4 iliac bone, 3 and sole of the foot. 2 Various hypotheses have been proposed regarding their possible origin, but none have been conclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, teratomas are categorized into 2 subtypes: mature and immature. Mature teratomas are considered benign tumors that can be cystic or solid, consisting of well-differentiated adult tissues from one or more germ cell layers [ 8 , 9 ]. Immature teratomas, on the other hand, are malignant tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Mature teratomas are reportedly more common than immature ones and immature congenital teratomas are considered extremely rare lesions. [ 5 , 8 , 10 ]. However, our case deviated from the norms mentioned earlier, as it occurred in the left hemisphere of the brain, involving temporal, parietal, and occipital brain lobes, and was far from the midline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation